2021
DOI: 10.1159/000519201
|View full text |Cite
|
Sign up to set email alerts
|

Revision Chiari Surgery in Young Children: Predictors and Outcomes

Abstract: <b><i>Introduction:</i></b> Children aged 0–6 years with Chiari malformation (CM) often present with atypical symptoms and require revision surgery more often than older children. We studied characteristics and outcomes of CM patients in this age-group who underwent one or more revision surgeries to assess how often revision surgery is necessary and successful in this age-group. <b><i>Methods:</i></b> We retrospectively reviewed patients who were diagnosed with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Basaran and Colleagues [27] reported a higher rate of complications in CM-1.5 than in CM-1. This finding was not confirmed by Chae and Greenfield [24], who reported no significant differences in the rate of reoperations. Patients with CM-1.5 would have more severe syndromes and shorter clinical histories [27] and may require different treatment modalities [14].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Basaran and Colleagues [27] reported a higher rate of complications in CM-1.5 than in CM-1. This finding was not confirmed by Chae and Greenfield [24], who reported no significant differences in the rate of reoperations. Patients with CM-1.5 would have more severe syndromes and shorter clinical histories [27] and may require different treatment modalities [14].…”
Section: Discussionmentioning
confidence: 55%
“…Reoperation due to failed treatment is a major problem in the management of CM-1 syndrome. All series show rates of treatment failures that are not negligible [7,11,[17][18][19][20][21][22][23][24][25][26]. However, the skillfulness of the surgeon may play a significant role: in the series of Walker-Palmer et al [26], the complication rate ranged from 11 to 20% for extradural, and 10.5 to 40% for intradural surgeries depending on the experience of the surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that recurrence of symptoms is the most common reason for reoperation and that there were improved outcomes clinically in most if not all of these young patients. 22 Case 5 of our series demonstrates a scenario where multiple surgeries were performed with apparent initial improvement, but currently with MRI appearances demonstrating a worsening scenario once again.…”
Section: Discussionmentioning
confidence: 90%
“…Chae and Greenfield 22 reported that of 45 patients who underwent decompressive surgery for Ch1, 8 (18%) required revision surgeries (1 or more) and 5 of these showed improvement or resolution after reoperation with no change seen in 3 (of which 2 underwent a third surgery with improvement in one case and none in the other, with the last patient being operated for the fourth time, and recurrence of symptoms a year later). They concluded that recurrence of symptoms is the most common reason for reoperation and that there were improved outcomes clinically in most if not all of these young patients 22 . Case 5 of our series demonstrates a scenario where multiple surgeries were performed with apparent initial improvement, but currently with MRI appearances demonstrating a worsening scenario once again.…”
Section: Discussionmentioning
confidence: 99%
“…Expanded studies of EDS and long COVID19 symptoms and outcomes-Systematic ascertainment of patient findings via the findings of S1 Table included few laboratory and no medical measures like the results of echocardiography-vascular screening [7], tilt-table [30,31], nerve conduction [13], intestinal motility [36], or imaging for Chiari [134], median arcuate ligament [135], or nutcracker changes [136] that lead to immediate therapies. Evaluation protocols adding the latter results could improve symptom descriptions [129] and outcome measures [130] for EDS and long COVID19 as done for COVID19 infection in patients with rheumatic diseases [131].…”
Section: Implications For Future Researchmentioning
confidence: 99%